Clinical impact of lifestyle interventions for the prevention of diabetes: an overview of systematic reviews - Howells, Lara (BMJ Open, 2016)
OBJECTIVES: To review the clinical outcomes of combined diet and physical activity interventions for populations at high risk of type 2 diabetes. DESIGN: Overview of systematic reviews (search dates April–December 2015). SETTING: Any level of care; no geographical restriction. PARTICIPANTS: Adults at high risk of diabetes (as per measures of glycaemia, risk assessment or presence of risk factors). INTERVENTIONS: Combined diet and physical activity interventions including ≥2 interactions with a healthcare professional, and ≥12 months follow-up. OUTCOME MEASURES: Primary: glycaemia, diabetes incidence. Secondary: behaviour change, measures of adiposity, vascular disease and mortality. RESULTS: 19 recent reviews were identified for inclusion; 5 with AMSTAR scores <8. Most considered only randomised controlled trials (RCTs), and RCTs were the major data source in the remainder. Five trials were included in most reviews. Almost all analyses reported that interventions were associated with net reductions in diabetes incidence, measures of glycaemia and adiposity, at follow-up durations of up to 23 years (typically <6). Small effect sizes and potentially transient effect were reported in some studies, and some reviewers noted that durability of intervention impact was potentially sensitive to duration of intervention and adherence to behaviour change. Behaviour change, vascular disease and mortality outcome data were infrequently reported, and evidence of the impact of intervention on these outcomes was minimal. Evidence for age effect was mixed, and sex and ethnicity effect were little considered. CONCLUSIONS: Relatively long-duration lifestyle interventions can limit or delay progression to diabetes under trial conditions. However, outcomes from more time-limited interventions, and those applied in routine clinical settings, appear more variable, in keeping with the findings of recent pragmatic trials. There is little evidence of intervention impact on vascular outcomes or mortality end points in any context. ‘Real-world’ implementation of lifestyle interventions for diabetes prevention may be expected to lead to modest outcomes.